An Analysis of the Arabic Language Proficiency of Students in Mahārah Al-Istima’ at an Islamic Senior High School - Ramadil, Muhammad; Musdizal, Musdizal (UIN Sunan Gunung Djati Bandung, 2024)
In Arabic, there are 4 skills (mahārah), one of which is istima' referring to the ability to listen or comprehend. This study examines the level of understanding of various types of texts, information processing speed, and the ability to recognize nuances in the spoken language. The focus on MAS Bhakti Kerapatan Jujun provides a unique cultural and educational context that may influence research outcomes and offers a new perspective on learning istima' skills in that environment. This research aims to evaluate the mastery level of istima' skills among 10th-grade students at MAS Bhakti Kerapatan Jujun. The research method used was a survey with data collected through interviews as the testing instrument. The study population consisted of all 10th-grade students at MAS Bhakti Kerapatan Jujun, and the researcher used a total sampling technique to gather data. The research results show that students' istima' abilities overall fall into the category of sufficient. The evaluation was conducted through six indicators, indicating that most students have fairly good abilities in identifying letters, distinguishing sounds, understanding vocabulary meanings, and providing responses. However, their ability to comprehend sentences and discourse remains categorized as inadequate. The implications of this study highlight the importance of enhancing students' istima' skills in understanding sentences and discourse in Arabic. Future research could explore more effective teaching strategies to improve students' comprehension of sentences and discourse within the unique cultural and educational context